2021
DOI: 10.47747/ijfr.v2i1.304
|View full text |Cite
|
Sign up to set email alerts
|

Status of Professional Skills in MBA Graduates, Its Challenges, and Way Forward in Kathmandu Valley: Evidence from Professional Skill Index

Abstract: Today's MBA courses are continuous preparation-based teaching-learning practice to meet the requirements that industries expect from MBA graduates and further enhance their skills and knowledge that would aid them to fit in the job market. Thus, this study tries to assess the status of professional skills in MBA graduates, its challenges, and the way forward with the help of a professional skill index. Based on descriptive analysis, this study is conducted among 280 employers who employ MBA graduates, and a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Employers' perceptions of the demand for professional skills among MBA graduates are investigated in this study. Bhandari et al (2021) stated that every organization seeks professional skills in MBA graduates while hiring them thus, they must be well prepared with various skills required to fit in any sort of organization. Chia and Holt (2008) in this regard stated that Universities and colleges graduates' students who are not prepared for organizational challenges in real world.…”
Section: Final Regression Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Employers' perceptions of the demand for professional skills among MBA graduates are investigated in this study. Bhandari et al (2021) stated that every organization seeks professional skills in MBA graduates while hiring them thus, they must be well prepared with various skills required to fit in any sort of organization. Chia and Holt (2008) in this regard stated that Universities and colleges graduates' students who are not prepared for organizational challenges in real world.…”
Section: Final Regression Resultsmentioning
confidence: 99%
“…Students, on the other hand, should equally support them. Then and only then will the process be productive (Bhandari et al, 2021). MBA students in Nepal have a lot of knowledge but are unable to use it.…”
Section: Final Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study emphasized the importance of collaboration among various stakeholders to ensure that students are adequately prepared for the workplace and possess the necessary employability skills to succeed. Likewise, Bhandari et al (2021) studied business graduate students' professional skills and found that employers search for professional qualities in applications. Both hard and soft skills are sought after by employers when hiring new employees from colleges and universities.…”
Section: Review Of Literaturementioning
confidence: 99%